Effect of sowing time and variety on seed germination and vigour index of wheat (Bangladesh Journal of Agricultural Research, 2016)
Experiments were carried out in research field and laboratory of Seed Technology Division, Bangladesh Agricultural Research Institute, Gazipur during rabi season of 2008-09 and 2009-10 to find out the effect of sowing time and variety on seed germination and vigour index of wheat after harvest of the crop. There were two sets of treatments, comprising a) three dates of sowing viz. 20 November, 5 December and 20 December; and b) three varieties viz. Bijoy, Sufi and Prodip. Split plot design and complete block design were followed in field and laboratory experiments, respectively. Results revealed that the highest seed germination 93.33% was recorded in Prodip sown on 20 December, 2008 and Bijoy sown on 5 December, 2009. However, all the varieties showed more than 83% seed germination at all dates of sowing of wheat. The highest vigour indices, 1.53 and 1.41 were found in the seeds of Sufi sown on 20 November in both the years of 2008 and 2009, respectively.Bangladesh J. Agril. Res. 41(1): 127-136, March 2016